Wissenschaft weltoffen 2023 Facts and Figures on the International Nature of Studies and Research in Germany and Worldwide - DAAD; DZHW (wbv Media, 2023)
This publication compiles and analyses the latest data on the international nature of studies, research and teaching in Germany and other major countries. The German Academic Exchange Service (DAAD) and the German Centre for Research on Higher Education and Science Studies (DZHW) have issued this standard reference work on international mobility in the higher education sector since 2001. The spotlights in this edition report on the retention of international students in their respective host countries, preparatory courses for university admission at Studienkollegs in Germany and the study-related international mobility of domestic students at German universities. The authors of the publication analyse and interpret developments relating to international students and researchers in Germany, the mobility patterns of students and researchers from Germany and international academic mobility worldwide. Wissenschaft weltoffen integrates the international data published by the OECD and UNESCO with the national data from the Federal Statistical Office. For over 20 years, in combination with other indicators and time series, the publication has provided a valid basis for analysing and monitoring the internationalisation of the higher education sector.